2016
DOI: 10.3233/xst-160567
|View full text |Cite
|
Sign up to set email alerts
|

Study on the relation between tissues pathologies and traditional chinese medicine syndromes in knee osteoarthritis: Medical image diagnostics by preoperative X-ray and surgical arthroscopy

Abstract: For knee osteoarthritis, different syndromes of traditional Chinese medicine presents different tissues pathological changes at the knee joint under arthroscopy, which will provide objective basis for the diagnosis of this medical condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The relationship between TM pattern descriptors and CM diagnosis has been an established research topic within the East Asian TM community (Lu and Chen, 2011;Lu et al, 2012). Studies have shown the relationship of specific TM pattern descriptors with a diverse array of CM presentations, including knee osteoarthritis (Tian et al, 2016) and openangle glaucoma (Yang et al, 2018). However, before the advent of the standardized TM ICD-11 pattern descriptors as in this study, it has been difficult to conduct a comparative analysis between differing medical traditions with unique terminology and classifications, and such as between Kampo and traditional Chinese medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between TM pattern descriptors and CM diagnosis has been an established research topic within the East Asian TM community (Lu and Chen, 2011;Lu et al, 2012). Studies have shown the relationship of specific TM pattern descriptors with a diverse array of CM presentations, including knee osteoarthritis (Tian et al, 2016) and openangle glaucoma (Yang et al, 2018). However, before the advent of the standardized TM ICD-11 pattern descriptors as in this study, it has been difficult to conduct a comparative analysis between differing medical traditions with unique terminology and classifications, and such as between Kampo and traditional Chinese medicine.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely used to treat various bone diseases in China for several decades [ 7 ]. According to TCM syndromes, the deficiency and blood stasis are regarded as the main pathogenesis of OA [ 8 ]. Of note, BSHX has been previously shown to dilate blood vessels and improve microcirculation, thereby modifying platelet aggregation, protecting vascular endothelial cells, and resisting oxidation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…TCM believes that KOA is associated with constitution, environment, diet, exercise and other factors, and the occurrence and development of the disease is a progressive process. TCM believes that dampness easily invades the body, especially in damp environments or living in cold regions [6] . Dampness can enter the body through the skin, accumulate in the joints, hinder the circulation of qi and blood, and lead to symptoms such as joint pain, swelling and stiffness.…”
mentioning
confidence: 99%